"O homem que ri: um estudo das representações do Coringa - Isabella Pereira Marucci (2023)
The purpose of this work is to analyze the construction of Batman's archenemy, the Joker, over the decades that follow his first appearance to the present day. The objective focuses on perceiving the elements that compose and form the character, who demonstrates complexity in the delimitation of his personality, such as, for example, due to the lack of a defined origin. In addition, its relationships with violence and insanity will also be discussed. Created as something fleeting in 1940, having Conrad Veidt's apparency in the man who laughs as one of its references, Joker remains alive in pop culture and walks through different narratives, from comics, to movies, series and video games. His presence triggers reflections around society and values, which the villain seeks to deconstruct, even questioning Batman's heroic bias. His numerous representations, although different from each other, allow us to recognize the clown prince of crime by maintaining the elements that configure him as such. The analysis is based on studies about the language of comics, audiovisual and violence and representation, based on authors such as Scott McCloud, Will Eisner, Jennifer Van Sijll, Ismael Xavier, Freud, Umberto Eco, Grant Morrison, among others. KEYWORDS: Joker; Batman; Comics; violence.